Review of current methods for estimating areal reduction factors applied to South African design point rainfall and preliminary identification of new methods - Pietersen, J.P.J.; Gericke, O.J.; Smithers, J.C.; Woyessa, Y.E. (Journal of the South African Institution of Civil Engineering, 2015)
Design point rainfall estimates assume a uniform distribution of rainfall over a catchment, and hence are only representative for a limited area. For larger areas, areal reduction factors (ARFs) are used to convert design point rainfall depths/intensities to an average areal design rainfall depth/intensity for a catchment-specific critical storm duration and catchment area. This paper presents a review of ARF estimation methods used nationally and internationally, with comparisons of the South African methods in the C5 secondary drainage region using standard input variables. The comparison of different ARF estimation methods confirmed that the empirical methods adopted for general use in South Africa are based on a limited database of observed rainfall data and are used without local correction factors beyond their original developmental regions. This results in the characterisation of the actual rainfall process over a catchment, and translation into questionable design peak discharge estimates. Therefore, the ARFs in South Africa need to be re-investigated in the light of recent extreme flood events, utilising the longer periods of record and denser rain-gauge networks which are now available for analysis. The variation of ARFs with return period and with rainfall producing mechanisms also needs to be investigated. Updated ARFs developed and verified using local rainfall data will improve the accuracy of design hydrology for large catchments in South Africa when eventbased rainfall-runoff deterministic methods are used.
Published Article
Keywords: areal reduction factor; areal design rainfall; critical storm duration; design point rainfall; return period